Toward the calibration of 2D thermomechanical simulations of magma poor passive continental margins: method, validation and case example - Perron, Paul; Le Pourhiet, Laetitia; Jourdon, Anthony; Cornu, Tristan; Gout, Claude (Comptes Rendus. Géoscience)
In recent decades, geodynamic modelers have aimed to comprehend key factors governing continental rifting, such as the extension rate, lithospheric thickness, Moho mechanical coupling, and mantle convection’s thermal influence. While prior models offered insights into rifting processes, they lacked the calibration to specific Earth regions. Introducing heterogeneities into the model does in some cases help to calibrate the simulation results to a geological data from a specific region. Acknowledging structural inheritance as a form of kinematic forcing in the models, and recognizing the challenge of anticipating and identifying all inherited geological structures present before rifting, a new modeling approach was devised. This method integrates a new kinematic module into the pTatin2D code, allowing for calibrating numerical simulations with regional geological and geophysical dataset over time while solving for mechanical balance using Stokes flow to ensure that crustal deformation remains consistent with mantle dynamics. By calibrating against a 2D cross-section extracted from the final state of a 3D model, we show that the approach predicts thermal history and deformation paths beyond calibration points. In particular, the thermo-mechanical feedback can help mitigate some uncertainties in the deformation path. Applied to Iberia–Newfoundland margins, the method demonstrates effectiveness in real-case scenarios, aligning with previous reconstructions by incorporating faults and lower crustal flow.